AB0438 MALIGNANCIES IN PATIENTS WITH PRIMARY SJOGREN'S SYNDROME. (2nd June 2020) - Özdemir Işik, Ö.; Yazici, A.; Cefle, A.
Abstract : Background: Sjogren's syndrome (SS) is a chronic, systemic, autoimmune disease. The risk of developing lymphoproliferative malignancies is high in primary Sjogren's syndrome(pSS). Objectives: In this study, we planned to present malignancy data in patients who were followed up in our outpatient clinic with a diagnosis of pSS. Methods: Data of 151 patients diagnosed with pSS between 2004-2019 were retrospectively reviewed and clinical, demographic characteristics of 15 patients diagnosed with malignancy were examined. Results: All 15 patients with malignancy were female, their mean age was 59 ± 13 years, and the disease duration was 9 ± 1 years. In this group, 7% of the patients had fever, 13% had weight loss and 7% had night sweats. Dry eye was present in 87%, dry mouth in 93%, LAP in 53% (Table 1 ). None of the patients had myositis, neuropathy and vasculitis. In 87% of the patients, schirmer was below 5 mm and in 67% of the salivary gland scintigraphy, decreased involvement in the parotid and submandibular gland was detected. Salivary gland biopsy was compatible with pSS diagnosis in 53% of patients. Rheumatoid factor, ANA, SS-A and SS-B were positive in %60, %93, %67 and %53 of patients, respectively. Low C3 level was detected in 27% of patients and C4 level was normal in all patients. Hypergammaglobulinemia was detected in%27 patents but data of five patients could not be reached. Malignancy was detected in 10% of the patients who were followed up with the diagnosis of PSS. Two patients had cervical cancer (CA), four had breast CA, three had thyroid papillary CA, one had diffuse large b cell lymphoma, one had MALT (mucous-associated lymphoid tissue) lymphoma, one had mycosis fungoides, one had vulva epithelial carcinoma and two had lung CA. Patients with malignancy and those without were compared in terms of clinical and laboratory findings. There was a significant relationship between presence LAP and smoking with development of malignancy. Subgroup analysis was performed according to titers of C-Reactive protein (CRP) and erythrocyte sedimentation rates (ESH), but there was no significant relationship between laboratory findings and the development of malignancy. (Table 2 ) Conclusion: According to 2015 data of Turkey unified database for all age groups, the rate of cancer in woman is 25% for breast cancer, 12% for thyroid CA, 5.1% for lung CA, 2.5% for cervical CA, 2.8% for non-hodgkin lymphoma. Patients with pSS have a 6 to 19-fold increased risk for the development of non-Hodgkin B-cell lymphoma. For these reasons, detailed questioning and physical examination gain importance in the follow-up of patients References: [1]E Theander, G Henriksson, O Ljungberg.Lymphoma and other malignancies in primary Sjögren's syndrome: a cohort study on cancer incidence and lymphoma predictors. Ann Rheum Dis. 65 (6):796-803 2006 Disclosure of Interests: None declared